Reappraising theorisations of power in the coach-athlete relationship: future directions for sports coaching research - Consterdine, A.; Taylor, W. G. (Sports Coaching Review, 2025)
This paper calls for a reconceptualisation of the manner in which we have considered and described the coach-athlete relationship in high-performance sport. We appeal for a radical reconsideration of the way that power has been portrayed within coaching literature in an attempt to consider new ways in which power operates in such arenas. Although theoretical work on power within the coaching process has been enlightening, and more recent empirical studies have demonstrated some interesting conceptualisations of power from a poststructural perspective, it has not been extensively applied in sufficient depth overall. By offering more nuanced poststructural and critical readings of power, together with a contextualised approach that considers interactions, language, entanglement, materiality, and discourse, it may be possible to suggest a more insightful set of ideas; one that allows us to better understand the nature of coach-athlete relationships operating at this level.